The Canaries’ Experience: saving lives through a true events based virtual reality experience a multidisciplinary approach using avatars in suicide prevention and intervention - Shalaby, Salma; Bifarin, Oladayo; Ward, Ryan; McCann, Niall; Saini, Pooja (Frontiers in Virtual Reality, 2026)
This paper outlines the conceptual foundation of The Canaries’ Experience, a PhD research project at Liverpool John Moores University focused on the development and evaluation of immersive technology for preventive mental health interventions. The project forms part of a broader interdisciplinary initiative that integrates artificial intelligence, virtual reality, immersive storytelling, and spatial audio to deliver personalised therapeutic experiences. Targeting individuals at risk of self-harm and suicide particularly in high-risk or isolated, confined, and extreme (ICE) environments it aims to enable early detection and mitigation of psychological distress. Situated at the intersection of mental health, digital therapy, and narrative design, the initiative highlights the potential of scalable, integrated approaches to enhance psychological resilience and promote cross-sector collaboration.